A Pia União das Filhas de Maria da cidade de Goiana, 1906-1920 - Silva, Maria de Fátima Santana da (2007)
The objective of this study is to analyze the appearance of the Pius Union of the Daughters of Mary in the city of Goiana in 1906 as a mechanism used by the romanizing bishops to control the popular expressions consider to be deviations by these prelates. At the end of the nineteenth century and at the beginning of the twentieth, religious congregations introuced new marian devotions as in the case of the Pious Union of the Daughters of Mary. Through theses associations the romanizing bishops will gain the control of the tradition forms of popular Catholicism and to establish norms of behavior of young women.